Spatial distribution of e-cigarette vending machines: a case study from Germany - Alemu, Sisay Mulugeta; Mons, Ute; Schaller, Katrin; Baltaci, Ezgi; Hoe, Connie (Tobacco control, 2025)
Background Germany has the highest density of cigarette vending machines globally, and the recent proliferation of electronic cigarette (e-cigarette) vending machines raises growing public health concerns, particularly regarding youth exposure. However, limited data exist on their spatial distribution and contextual placement. This study presents the first spatial analysis of e-cigarette vending machines in Germany, using the Berlin-based company ‘Vape4Me’ as a case study. - Methods Geo-referenced data on e-cigarette vending machine locations were extracted from the Vape4Me website and cross-validated using Google Maps and Microsoft Bing Maps. Spatial analyses—including density mapping, proximity assessments and co-location analysis—were conducted using ArcGIS Pro, R and OpenRouteService. Associations with population size were examined through regression analysis. Selected sites in Cologne and Wiesbaden were visited for on-site validation. - Results A total of 316 (Vape4Me) e-cigarette vending machines were identified in Germany, with the highest concentration in Berlin. Machine density was significantly associated with population size, with a 3.24% increase per 1000 additional residents. In Berlin, vending machines were frequently co-located with hospitality and commercial establishments and rarely placed near outdoor or public utility areas. On-site inspections revealed that machines offered disposable e-cigarettes for around €10, with basic age verification. - Conclusion The integration of e-cigarette vending machines into everyday environments—combined with continuous advertising and 24/7 access—normalises e-cigarette use and poses challenges to tobacco control efforts. Stronger regulations, including bans on the sale of cigarettes and e-cigarettes via vending machines, are urgently needed to protect youth from early nicotine exposure.
Gesehen am 12.02.2026